Evaluation of the Patient Safety Improvement Corps Experiences of the First Two Groups of Trainees - Teleki, Stephanie S. (RAND Corporation, 2006)
An evaluation of the first two years of the Agency for Healthcare Research and Quality and Veterans' Affairs' Patient Safety Improvement Corps program for improving health care professionals' patient-safety knowledge and skills. Data were collected through in-person interviews at the final training session, and through telephone follow-up interviews one year later. Overall, participants valued the tools and skills they learned and continue to use.